2015
DOI: 10.4103/0974-8490.150520
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and bioactivities of Glinus oppositifolius

Abstract: Objectives:To isolate the secondary metabolites from the dichloromethane (DCM) extracts of Glinus oppositifolius; to test for the cytotoxicity of a new triterpene, oppositifolone (1); and to test for the hypoglycemic, analgesic, and antimicrobial potentials of 1, DCM and aqueous leaf extracts of G. oppositifolius.Methods:The compounds were isolated by silica gel chromatography and identified by nuclear magnetic resonance spectroscopy. The cytotoxicity potential of 1 was tested using the 3-(4,5-dimethylthiazol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…In the US NCI plant screening program, a crude extract is supposed to have in vitro cytotoxic activity following incubation between 48 h and 72 h if the GI 50 value in carcinoma cells is less than 20 μg/mL. [ 6 7 ]…”
Section: Resultsmentioning
confidence: 99%
“…In the US NCI plant screening program, a crude extract is supposed to have in vitro cytotoxic activity following incubation between 48 h and 72 h if the GI 50 value in carcinoma cells is less than 20 μg/mL. [ 6 7 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, we cannot exclude the possibility that some of the isolated compounds might be artifacts resulted from the extraction treatment, for example compound 23 might be artifacts of ethanol extraction. The triterpenoids and their glycosides were hopane-type and oleanane-type which have been proofed to be existing in this plant [9,13]. Four compounds including glinusopposide B ( 6 ), glinusopposide Q ( 21 ), glinusopposide T ( 24 ), and glinusopposide U ( 25 ) showed considerable inhibitory activities against M. gypseum and T. rubrum .…”
Section: Discussionmentioning
confidence: 99%
“…It is used to treat leprosy, leukoderma, heart, and skin diseases in the traditional medicine of Myanmar [5]. The major secondary metabolites from G. oppositifolius are triterpenoids and their glycosides, which exhibit α-glucosidase inhibitory [8], cytotoxic [9], and antiprotozoal activities [10]. There is little research reported the anti-fungal activities of G. oppositifolius .…”
Section: Introductionmentioning
confidence: 99%
“…Some of them exhibit activity against flatworms of the order trematodes (Cheeseman & Cooksen, 1979). Ragasa, Tepora, and Rideout (1998) reported that 6-(1-hydroxyethyl)-7,8 dimethoxy-2,2dimethylchromene and 6hydroxy-7,8 dimethoxy-2,2-dimethylchromene are the derivatives of 2,2-dimethylchromene, which showed antimicrobial activity (Inte, Ragasa, & Rideout, 1998).…”
Section: Essential Oil Metabolites and Their Pharmacological Propermentioning
confidence: 99%